Enhancing Individual Critical Thinking and Collaborative Skills: A CinQASE-Based Interactive E-Module for Physics Education - Hunaidah Hunaidah; Sitti Kasmiati; Erniwati Erniwati; Nilawati Ute; Md Asri bin Ngadi (FKIP Universitas Lampung, 2026)
This study aims to develop an e-module based on the CinQASE learning model supported by Flip PDF Professional and evaluate its effectiveness in improving students' Individual Critical Thinking (InCT) and collaborative skills in Momentum and Impulse materials. This study employed an R&D approach based on the 4D development model (Define, Design, Develop, Disseminate), comprising four main stages. In the Define stage, a needs analysis was conducted to identify the essential competencies and materials aligned with the curriculum and students' needs. The Design stage focused on designing the e-module structure, determining learning strategies, and compiling learning components, including worksheets and supporting media. The Develop stage included product development, validation by subject matter and media experts, and revisions based on feedback to ensure content quality and suitability. The Disseminate stage was conducted through limited and extensive trials to assess the practicality, readability, and effectiveness of e-modules in real-world learning contexts. Research instruments included expert validation sheets, student and teacher response questionnaires, collaborative activity observation sheets, and InCT tests to assess individual improvements in critical thinking skills. The results showed that the e-module had very high validity across construct, content, graphics, electronic media, materials, presentation, and language, and was considered practical and easy to use by both students and teachers. N-Gain analysis indicated a significant increase in all InCT indicators, from the moderate category in limited tests (0.40–0.45) to the high category in extensive tests (0.68–0.74). Collaborative activities through CinQASE indicator-based worksheets proved effective in encouraging active participation, critical discussion, and peer evaluation. These findings indicate that CinQASE-based e-modules supported by Flip PDF Professional serve as effective interactive learning media for improving students' critical and collaborative thinking skills, while also providing an engaging, flexible, and accessible learning tool for both teachers and students. Keywords: CinQASE, e-modul, Flip PDF, critical thinking skills, collaborative abilities, momentum, and impulse.